Pengembangan Kapasitas Aparatur Gampong terkait Penyelesaian Perkara melalui Peradilan Adat - Mansari, Mansari; Rizkal, Rizkal; Hadana, Erha Saufan; Nurjannah, Via; Irwansyah, Irwansyah; Hakim, Lukman; Haikal, Muhammad; Ruslaini, Ruslaini; Isa, Muhammad; Hidayat, Rahmad; Bahri, Samsul; Ikhsan, Ikhsan; Fitriliana, Fitriliana (Abdurrauf Journal of Community Service, 2025)
This community service program was carried out to strengthen the capacity of Lam Lumpu Village officials in resolving disputes through customary justice, which has long been the main mechanism for maintaining social harmony. The identified issues include limited understanding of the legal foundations regulated in the qanun and national legislation, case resolution procedures, mediation techniques, and weaknesses in systematically preparing case documents. Through participatory training, field observations, and intensive mentoring, the program focused on improving the technical skills and professional conduct of village officials in handling various types of customary disputes.  The results of the program show a significant improvement in the understanding of customary law as regulated in the Qanun, as well as in the ability to apply mediation techniques supported by effective communication, thereby providing better solutions for the community. [Kegiatan pengabdian kepada masyarakat ini dilaksanakan untuk memperkuat kapasitas aparatur Gampong Lam Lumpu dalam penyelesaian sengketa melalui peradilan adat yang selama ini menjadi mekanisme utama dalam menjaga keharmonisan masyarakat. Permasalahan yang diidentifikasi yaitu pemahaman terhadap dasar hukum yang diatur dalam qanun dan peraturan perundang-undangan, prosedur penyelesaian perkara, teknik mediasi, serta lemahnya kemampuan dalam menyusun dokumen perkara secara sistematis. Melalui pendekatan pelatihan partisipatif, observasi lapangan, pendampingan intensif, kegiatan ini difokuskan pada peningkatan keterampilan teknis dan sikap profesional aparatur dalam menangani berbagai bentuk sengketa adat. Hasil kegiatan menunjukkan adanya peningkatan signifikan pada aspek pemahaman hukum adat yang diatur dalam Qanun, kemampuan menerapkan teknik mediasi berbasis komunikasi efektif sehingga memberikan solusi yang terbaik bagi masyarakat.]